A gazdasági átalakulás tapasztalatai Csehországban, Szlovákiában, Lengyelországban és az egykori Német Demokratikus Köztársaságban (1990-2000) - Domonkos, Endre (Közép-Európai Közlemények, 2024)
During the period from 1989 to 1990, economic and political transition in Central and Eastern Europe was accompanied by the general liberalisation and opening up of markets to foreign investors. This process started at the end of the 80s, which coincided with the general crisis of “state socialism” in the region. It is worth mentioning that there were substantial differences in the creation of a free market economy among the Central and Eastern European countries. Whereas Poland applied shock treatment based on the general principles of the Washington Consensus, Czechoslovakia followed a double policy by pursuing the concept of neoliberal economic policy and the road of “gradualism” to avoid the negative impacts of the transformation process such as the emergence of mass unemployment and bankruptcy of state-owned companies. As a result of the Treaty Establishing a Monetary, Economic and Social Union, the German Democratic Republic became an organic part of the Federal Republic of Germany in 1990, which required the introduction of liberalisation measures. Although the Central and Eastern European countries followed a different road in the creation of a free enterprise market economy in the 1990s, but by the turn of the millennium due to the privatisation of state-owned assets, privately held companies accounted for 70 per cent of GDP, whilst the share of the state sector was 30 per cent. The objective of the paper is to highlight the experiences of economic transition in the Czech Republic, Slovakia, Poland and in the former German Democratic Republic (GDR) by comparing its main characteristics and stages. Besides macroeconomic stabilisation, emphasis will be placed on evaluating the achievements of privatisation and its main consequences. Due to length constraints, the essay will not focus on the social impacts of the transformation process in Central and Eastern Europe.